Pengembangan Sistem Kontrol Penggerak Stang Las Pada Sliding Adaptive Two Axis Mesin Pengelasan Smaw Berbasis Mikrokontroller Arduino Uno - Surya Dita Prasetya; Yohannes Yohannes (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
SMAW (Shield Metal Arc Welding) is a welding technique using electric current that forms a current arc and webbed electrodes. In the SMAW welding process there are parameters that determine the quality of the welding results. This welding handlebar drive control system is made to simplify work, especially in the field of welding and get constant parameters. The research method is used the working principle of CNC 2 axis machines. The CNC 2 axis machine is able to move in the direction of the X and Y axis in the work plane and have high precision and precision. This welding handlebar drive control system is controlled by Universal G-Code Sender software. Making microcontroller-based welding handlebar drive control systems makes changes to the metal welding process easier, because operators only input data as desired. From the test results of the X and Y axis movements get the same results between the program and the actual, X and Y axis joint movements, limit switch testing and sliding movement speed that get results in the form of graphs and Tabels.Keywords : SMAW, Control System, Microcontroller ATMega 328P, Limit Switch, Arduino UNO